2016
DOI: 10.3109/17518423.2016.1139008
|View full text |Cite
|
Sign up to set email alerts
|

Stability of stereognosis after pediatric repetitive transcranial magnetic stimulation and constraint-induced movement therapy clinical trial

Abstract: Objective Poor sensibility affecting stereognosis, the ability to discriminate objects without visual input, can potentiate disuse of the paretic limb following stroke. The purpose of this study was to examine potential change in stereognosis after intervention. Methods Stereognosis testing in a secondary subgroup of 10 children with hemiparesis and baseline stereognosis deficits (ages 11–16) after a 13-day clinical trial of real or sham repetitive transcranial magnetic stimulation (rTMS) and constraint-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In addition, the improvement of hand movements might have enhanced participants' exploration during stereognosis assessments. Changes of stereognosis in relation to improved hand movements following the constraint-induced movement therapy has been shown in individuals who experience chronic stroke (Rich et al, 2017). As some components of the tasks practiced in the present study were task-specific training, the Bobath therapy demonstrated a similar change to constraint-induced movement therapy.…”
Section: Sensory Modalitiessupporting
confidence: 66%
“…In addition, the improvement of hand movements might have enhanced participants' exploration during stereognosis assessments. Changes of stereognosis in relation to improved hand movements following the constraint-induced movement therapy has been shown in individuals who experience chronic stroke (Rich et al, 2017). As some components of the tasks practiced in the present study were task-specific training, the Bobath therapy demonstrated a similar change to constraint-induced movement therapy.…”
Section: Sensory Modalitiessupporting
confidence: 66%
“…Conversely, pinching or grasping an object until perceived resistance neither requires verbalization nor involves deliberate recruitment of attentional networks. Such measures as stereognosis and/or grating orientation tasks were recently shown to improve with both intensive CIMT and bimanual training [ 36 , 40 ]. However, those studies were carried out in children older (>8 years of age) than those tested here, and even therein, stereognosis improvements were not always reliable.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] One study found stereognosis specific improvement following combined CIMT and repetitive transcranial magnetic stimulation (rTMS). [16] Due to the bimodal approach of this study, it remains unclear whether CIMT independently can induce sensory specific changes. Changes in proprioception and kinesthesia have yet to be evaluated and may play important roles in CIMT in HCP.…”
Section: Introductionmentioning
confidence: 95%